(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The article discusses the organization of physical circles in schools, shows how simple fun activities in circles and the disclosure of their meaning can increase students’ interest in physics and connect science with practice. The article explains the mechanism and essence of several experiments